2020
DOI: 10.3329/bjpsy.v30i2.45363
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic profile and psychiatric morbidities of suicide attempters: a cross-sectional observation in a tertiary care hospital of Bangladesh

Abstract: Nearly 800,000 people die due to suicide every year, which is 1 person every 40 seconds. In 2015, suicide alone accounted for 1.4% of all deaths worldwide, making it the 17th leading cause of death. 1 60% of these occur in Asia as estimated. 1 A recent review of suicide in Asia demonstrates higher average suicide rates in Asia compared to high-income countries. 2 Despite the fact that it is an enormous public health issue, suicide receives relatively less attention.According to the latest data published in may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…A similar study conducted in Kashmir in 2010 14 showed 15% of cases had personality disorders in their study sample. Another study conducted by Roy et al 24 in Bangladesh in 2018 had personality disorders in 7% of their study population which is close to the results in our study.…”
Section: Discussionsupporting
confidence: 92%
“…A similar study conducted in Kashmir in 2010 14 showed 15% of cases had personality disorders in their study sample. Another study conducted by Roy et al 24 in Bangladesh in 2018 had personality disorders in 7% of their study population which is close to the results in our study.…”
Section: Discussionsupporting
confidence: 92%
“…13,14 Another study done by Paresh Chandegara et al at India which is inconsistent with our study where Male cases were highest in number than Female cases (62.84% & 37.15% respectively) and common age group was 21 to 30 years (37.7%). 15 212 Table-II:…”
contrasting
confidence: 97%
“…This result is in concordance with the study results of Shoib et al (59.92%), Manhas et al (56.8%) and Roy, et al (73%). 18,20,24 This result may be explained by the fact that rural areas have low literacy rates and higher unemployment rates which is further complicated by financial difficulties and low socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%